Drinking Locally: A Water 87Sr/86Sr Isoscape for Geolocation of Archeological Samples in the Peruvian Andes - Scaffidi, Beth K.; Tung, Tiffiny A.; Gordon, Gwyneth; Alaica, Aleksa K.; González La Rosa, Luis Manuel; Marsteller, Sara J.; Dahlstedt, Allisen; Schach, Emily; Knudson, Kelly J. (Frontiers in Ecology and Evolution, 2020)
The analysis of 87Sr/86Sr has become a robust tool for identifying non-local individuals at archaeological sites. The 87Sr/86Sr in human bioapatite reflects the geological signature of food and water consumed during tissue development. Modeling relationships between 87Sr/86Sr in human environments, food webs, and archaeological human tissues is critical for moving from identifying non-locals to determining their likely provenience. In the Andes, obstacles to sample geolocation include overlapping 87Sr/86Sr of distant geographies and a poor understanding of mixed strontium sources in food and drink. Here, water is investigated as a proxy for bioavailable strontium in archaeological human skeletal and dental tissues. This study develops a water 87Sr/86Sr isoscape from 262 samples (220 new and 42 published samples), testing the model with published archaeological human skeletal 87Sr/86Sr trimmed of probable non-locals. Water 87Sr/86Sr and prediction error between the predicted and measured 87Sr/86Sr for the archaeological test set are compared by elevation, underlying geology, and watershed size. Across the Peruvian Andes, water 87Sr/86Sr ranges from 0.7049 to 0.7227 (M = 0.7081, SD = 0.0027). Water 87Sr/86Sr is higher in the highlands, in areas overlying older bedrock, and in larger watersheds, characteristics which are geographically correlated. Spatial outliers identified are from canals, wells, and one stream, suggesting those sources could show non-representative 87Sr/86Sr. The best-fit water 87Sr/86Sr isoscape achieves prediction errors for archaeological samples ranging from 0.0017 – 0.0031 (M = 0.0012, n = 493). The water isoscape explains only 7.0% of the variation in archaeological skeletal 87Sr/86Sr (R2 = 0.07), but 90.0% of archaeological skeleton 87Sr/86Sr fall within the site isoscape prediction ± site prediction standard error. Due to lower sampling density and higher geological variability in the highlands, the water 87Sr/86Sr isoscape is more useful for ruling out geographic origins for lowland dwellers than for highlanders. Baseline studies are especially needed in the highlands and poorly-sampled regions. Because the results demonstrate that a geostatistical water model is insufficient for fully predicting human 87Sr/86Sr variation, future work will incorporate additional substrates like plants, fauna, soils, and dust, aiming to eventually generate a regression and process-based mixing model for probabilistic geolocation of Andean samples.